The east face of helicon: West Asiatic elements in Greek poetry and myth - West, M. L. (Oxford Oxford university press, 1997)
Over the last sixty years scholars have increasingly become aware of links connecting early Greek poetry with the literatures of the ancient Near East. Martin West's new book far surpasses previous studies in comprehensiveness, demonstrating these links with massive and detailed documentation and showing they are much more fundamental and pervasive than has hitherto been acknowledged. - ;Ever since Neolithic times Greek lands lay open to cultural imports from western Asia: agriculture, metal-working, writing, religious institutions, artistic fashions, musical instruments, and much more. Over the last sixty years scholars have increasingly become aware of links connecting early Greek poetry with the literatures of Mesopotamia, Anatolia, Canaan, and Israel. Martin West's new book far surpasses previous studies in comprehensiveness, demonstrating these links with massive and detailed documentation and showing that they are much more fundamental and pervasive than has hitherto been acknowledged. His survey embraces Hesiod, the Homeric epics, the lyric poets, and Aeschylus, and concludes with an illuminating discussion of possible avenues of transmission between the orient and Greece. He believes that an age has dawned in which Hellenists will no more be able to ignore Near Eastern literature than Latinists can ignore Greek. -